First concrete documentation for presence of Aedes (Stegomyia) albopictus in Bolivia: dispelling previous anecdotes - Lardeux, Frédéric; Boussès, Philippe; Tejerina-Lardeux, Rosenka; Berger, Audric; Barnabé, Christian; Garcia, Lineth (Memórias do Instituto Oswaldo Cruz, 2024)
The presence of Aedes albopictus in Bolivia has been a subject of controversy, with a lack of concrete documentation. This study aimed to provide evidence of Ae. albopictus presence in Bolivia. Larval habitats were sampled in Rosario del Yata and San Agustín, Guayaramerín Municipality, Beni Department, northern Bolivia. Collected mosquito larvae were reared to the L4 and adult stages for morphological identification, with some specimens sequenced for confirmation. Aedes albopictus was identified in multiple larval habitats within peridomestic areas, such as buckets, canisters, and cut plastic bottles used as flower vases in both localities, confirming its establishment in the area. This represents the first concrete documentation of the species in Bolivia. The collections (larvae and adults) have been deposited in the Medical Entomology Laboratory of the Universidad Mayor de San Simón in Cochabamba, Bolivia, and the Laboratory of Entomology of the Instituto Nacional de Laboratorios de Salud of the Ministry of Health in La Paz, Bolivia. Given its role as a vector for arboviruses such as dengue and Chikungunya, Ae. albopictus should be incorporated into the Bolivian National Programme of Vector Control for monitoring.